Interior Revitalization of Indonesian National Building Gresik with Art Deco Themed Damar Kurung - Dhimastahta Dhanar Gumilang; Sumarno Sumarno; Harmilyanti Sulistiyani (Pendhapa, 2021)
The Interior Revitalization Planning at the Indonesia  National Building in Gresik by adapting Art Deco Style with the theme " Damar Kurung" is en effort to conserve a public space which is a performance building. The building so far tends to be underutilized due to various things, one of which is the condition of the building and its interior which is no longer feasible. Revitalization of important buildings is carried out as an effort to maintain the sustainability of architectural buildings as part of the culture of the people. The activities that are accommodated mainly are traditional arts. Revitalization by utilizing the building as a center for cultural activities for the people of Gresik and its surroundings. This design adopts an art deco style with damar kurung as the theme applied in the interior. Research using the Kurtz programming method. The design includes lobby, canteen, office, control room, auditorium, stage, dressing room, and backstage.